The Meanings of Vittorio’s Dreams in Vittorio, The Vampire - Alex Jhon (Humaniora, 2011)
The novel Vittorio, the Vampire has a deep interest in dream. Using Freudian Dream Theory, it can be classified for Vittorio’s dreams. The focuses are Vittorio’s dreams for the meanings. Vittorio is the protagonist of Anne Rice’s novel, ‘Vittorio, the Vampire’ and the novel is a vampire romance genre. The article is analyzing the novel through library research. The main classifications of dreams are focused on the symbols from Vittorio’s dreams. Using the Dream-work processes, the symbols then classified into more specific contents classifications. Each symbol in the Flower Meadow dream then classified thoroughly. There is another dream which is his Siblings’ Severed Heads but, the focus will be more to the meadow. From the symbols, then Vittorio’s feelings throughout the novel are classified. The findings of the classifications are more on Vittorio’s love with the female protagonist, Ursula.